2018
DOI: 10.1007/s12640-018-9968-1
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Grade Inflammation Aggravates Rotenone Neurotoxicity and Disrupts Circadian Clock Gene Expression in Rats

Abstract: A single injection of LPS produced low-grade neuroinflammation leading to Parkinson’s disease (PD) in mice several months later. Whether such a phenomenon occurs in rats and whether such low-grade neuroinflammation would aggravate rotenone (ROT) neurotoxicity and disrupts circadian clock gene/protein expressions were examined in this study. Male rats were given two injections of LPS (2.5–7.5 mg/kg), and neuroinflammation and dopamine neuron loss were evident 3 months later. Seven months after a single LPS (5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Circadian-disrupted mice had severe neuroinflammation and a greater degradation of motor skills, indicating that circadian dysfunction is a potential risk factor for PD. This effect was recapitulated in a rat model, where PD pathology was induced or exacerbated in one of three ways: by injection of lipopolysaccharide, injection of rotenone, or injection of both reagents ( Li et al, 2019 ). All three groups exhibited similar loss of dopaminergic neurons and neuroinflammation.…”
Section: α-Synuclein Proteinopathiesmentioning
confidence: 92%
“…Circadian-disrupted mice had severe neuroinflammation and a greater degradation of motor skills, indicating that circadian dysfunction is a potential risk factor for PD. This effect was recapitulated in a rat model, where PD pathology was induced or exacerbated in one of three ways: by injection of lipopolysaccharide, injection of rotenone, or injection of both reagents ( Li et al, 2019 ). All three groups exhibited similar loss of dopaminergic neurons and neuroinflammation.…”
Section: α-Synuclein Proteinopathiesmentioning
confidence: 92%
“…2 b). These results demonstrated that Mn injections induced chronic neuroinflammation in rats causing delayed loss of THir neurons in SNpc, a brain region sensitive to Mn and LPS intoxication [ 25 , 26 ]. It should be noted that in this study, 20% rats in the Mn 2+ 5 mg/kg group died, which could have more severe injury than surviving rats.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were countered in a double-blind manner. Data were expressed as percentage to saline-injected controls [ 26 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a DST shift effect analysis, one should keep in mind that there are two distinct phenomena in play: (1) the natural variation of day length, the amount of light over the year, and the daily sunlight intensity cycle affects the human circadian clock, behavior, and numerous diseases [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and; (2) the disruption of individuals' daily schedule due to the DST shift. Our analyses were designed to target the effects associated with the latter, adjusting for the former with negative controls.…”
Section: Plos Computational Biologymentioning
confidence: 99%